?????? ????? ?????? ??? ???? ???? ?????? ???????? ???????? ????????? ???????? ???????? ( Poster Session ) ?????? ????? ????? ???? ?????? - Atika Rochma Sari; Hisbullah Huda; Wahib Wahab (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
Abstrack: Speaking skill in learning a foreign language is very important skill for every student to master. Poster session is one of the teaching methods that can improve students’ ability to speak a foreign language. Therefore, innovative learning strategies are needed in order to stimulate students to be more active and confident in speaking. This research was conducted at Mts Negeri Sidoarjo with class VIII as the sample. This study is quantitative research using data and numbers to collect data. Data collection techniques used in this study were test, observations, interviews, questionnnaires and documentation in obtaining data relating to research. The purpose of this study was to ind out how high the effectiveness of the application of the poster session method in improving the speaking skills o class VIII students of MTs Negeri Sidoarjo.